Infrared emission of z ∼ 6 galaxies: AGN imprints. Issue 2 (26th February 2021) - Di Mascia, F; Gallerani, S; Behrens, C; Pallottini, A; Carniani, S; Ferrara, A; Barai, P; Vito, F; Zana, T
ABSTRACT: We investigate the infrared (IR) emission of high-redshift ( z ∼ 6), highly star-forming (SFR100 M_ yr^-1 ) galaxies, with/without active galactic nuclei (AGN), using a suite of cosmological simulations featuring dust radiative transfer. Synthetic spectral energy distributions (SEDs) are used to quantify the relative contribution of stars/AGN to dust heating. In dusty ( M d ≳ 3 × 10 7 M⊙ ) galaxies, ≳50–90 per cent of the ultraviolet (UV) radiation is obscured by dust inhomogeneities on scales ≳100 pc. In runs with AGN, a clumpy, warm (≈250 K) dust component coexists with a colder (≈60 K) and more diffuse one, heated by stars. Warm dust provides up to 50 per cent of the total infrared (IR) luminosity, but only 0.1 per cent of the total mass content. The AGN boosts the MIR flux by 10–100 times with respect to star-forming galaxies, without significantly affecting the far-IR. Our simulations successfully reproduce the observed SED of bright ( M UV ∼ −26) z ∼ 6 quasars, and show that these objects are part of complex, dust-rich merging systems, containing multiple sources (accreting black holes and/or star-forming galaxies) in agreement with recent HST and ALMA observations. Our results show that the proposed ORIGINS missions will be able to investigate the mid-IR (MIR) properties of dusty star-forming galaxies and to obtain good-quality spectra of bright quasars at z ∼ 6. Finally, the MIR-to-FIR flux ratio of faint ( M UV ∼ −24) AGN is >10 times higher than for normal star-forming galaxies. This implies that combined JWST /ORIGINS/ALMA observations will be crucial to identify faint and/or dust-obscured AGN in the distant Universe.